Analisis Aktivitas Kontraksi Uterus dan Perinatal Outcome pada Ibu Bersalin dengan Induksi - Shinta Wurdiana Rhomadona; Melyana Nurul Widyawati (Jurnal Keperawatan Silampari, 2019)
The purpose of this study is to analyze the activity of uterine contractions and perinatal outcomes in mothers who give birth by induction. The method of this study was a prospective observational descriptive design of 20 women with induction whose contractions were monitored every 15 minutes for 10 minutes by palpation and recorded perinatal outcomes. The results of this study show that the frequency and duration trends in successful induction deliveries tend to increase while those that fail tend to be constant. Successive average frequency and duration of successful induction 4.2 times / 10 minutes and 45.09 seconds. Whereas the failed induction was 1.92 times / 10 minutes and 25.54 seconds. In conclusion, most BLB is between 2500-4000 grams. The majority sex is female. Apgar score condition between 7-10. 1 baby serotinus and no baby with pathological jaundice. Keywords: Activity of Uterine Contraction, Labor Induction, Perinatal Outcome